2010
DOI: 10.1371/journal.pgen.1000844
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Rewiring of the Sex Determining dmrt1 Gene Duplicate by Transposable Elements

Abstract: Control and coordination of eukaryotic gene expression rely on transcriptional and posttranscriptional regulatory networks. Evolutionary innovations and adaptations often require rapid changes of such networks. It has long been hypothesized that transposable elements (TE) might contribute to the rewiring of regulatory interactions. More recently it emerged that TEs might bring in ready-to-use transcription factor binding sites to create alterations to the promoters by which they were captured. A process where … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
105
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(107 citation statements)
references
References 60 publications
2
105
0
Order By: Relevance
“…This evolutionary process was associated with the insertion of a transposable element called Izanagi that confers a novel expression pattern upon DMY/ dmrt1bY (Herpin et al, 2010). Unexpectedly, in our study, sexually different characters of germ cells were not impaired by knockdown and overexpression of DMY/dmrt1bY.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…This evolutionary process was associated with the insertion of a transposable element called Izanagi that confers a novel expression pattern upon DMY/ dmrt1bY (Herpin et al, 2010). Unexpectedly, in our study, sexually different characters of germ cells were not impaired by knockdown and overexpression of DMY/dmrt1bY.…”
Section: Discussionsupporting
confidence: 47%
“…Many studies indicate that the medaka (Oryzias latipes) sex chromosome arose relatively recently (Herpin et al, 2010;Kondo et al, 2004;Myosho et al, 2012;Takehana et al, 2007) and is not as differentiated as in mammals, in which sexual plasticity is much reduced in germ cells (e.g. Lavery et al, 2011;Koopman et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of many recent findings, we now consider that TEs have considerably shaped the structure, function, and evolution of the genomes and that the regulatory sequences that they possess can interfere with the networks of regulation of many genes, even of genes located at some distance from them (Feschotte 2008;Herpin et al 2010). TEs must therefore be considered to be integrated components of the genomes, which have played a major role in evolution.…”
Section: Transposable Elements As Players In Evolutionmentioning
confidence: 99%
“…3 Repetitive elements are important for the genome structure and function. [4][5][6] For example, satellite DNAs play a role in chromosome segregation during the cell cycle and comprise the centromeres of chromosomes, which bind microtubules. 7 Furthermore, both types of repeats can control gene expression on transcriptional and post-transcriptional regulatory networks.…”
mentioning
confidence: 99%
“…7 Furthermore, both types of repeats can control gene expression on transcriptional and post-transcriptional regulatory networks. [4][5][6] Studies demonstrated that satellite DNA plays a role in position-effect variegation and that TEs had been coopted to serve gene regulatory functions for the host, a process that fits under the term ''molecular exaptation. '' 8 Several methods are used to isolate repetitive DNA sequences.…”
mentioning
confidence: 99%